Trânsito e mobilidade urbana: utilização de geotecnologias para espacialização de acidentes em Ituiutaba/MG - Alves Neto, Fausto Amador (2016)
The number of car accidents in Brazil is a recurring theme of study, given that, according to research from the World Health Organization (WHO), has been considered the fifth country in the world with more traffic deaths. Among the main causes of accidents, the great growth of the fleet of vehicles associated with negligence, incompetence and recklessness in the conduct thereof, appears to have great representation in this scenario. This research aimed to know the areas of higher incidence of traffic accidents in the district center of the city of Ituiutaba / MG, comparing data from 2004 and 2014 provided by the Fire Department of Minas Gerais Military (CBMMG) and the Military Police of Minas Gerais (PMMG), writing down some of its possible causes. The objective was to also consider whether any increase in population and vehicle fleet in the selected period, would be linked to accidents variables in order to identify numbers of records, their main types, proceeding still mapping, through the arising of geotechnology tools, areas most frequent and presenting proposals for potential reduction of its quantitative. In the meantime, the methodology adopted was based on a literature review, documentary and field with quantitative and qualitative approach. The processing of the data, was given through the pursuit of literature which supported the study, linked to the current legislation, and also in the preparation of charts, tables and maps arising from the data provided by official agencies. Through the income earned, it was diagnosed that between the years was inclined population growth of 12.34% in Ituiutaba, while the increase of vehicle fleet was higher, a percentage of almost 126%, with the increase of motorcycles, scooters and mopeds the most significant (169,55%), and thus recorded higher recurrence rate in their involvement in accidents. The total received by both CBMMG as the PMMG, it was found that 28% of acidentarios records occur in the center, specifically within the range of 12:00 and 13:59, correlated to the increased use of central trade and public facilities. As for the possible causes of accidents raised in the reports raised the hypothesis of unreliability in these indicative given the imprecision spent in completing this item in the police reports. The mapping of the most repeated accidents pathways observed in public sites 17, 20, 26 and 07, respectively, greater concern about the quantitative earned. Finally, they suggested to some actions and proposals for the problem mitigation, among them educational lectures and preparation of educational / informational materials to be conducted at the National Traffic Week, established annually in the month of September each year, raising awareness, especially, future vehicle drivers about the importance of promoting road safety.